The Influence Of Principal Managerial Competency And Teacher Work Motivation On Teacher Performance At State Middle School 1 Airmadidi - Prisilia Debora Mangkang; Shelty DM Sumua; Henny Nikolin Tambingon (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Mangkang, Debora, Prisilia. 2026. The Influence of Principal Managerial Competence and Teacher Work Motivation on Teacher Performance at SMP Negeri 1 Airmadidi. Thesis, Educational Management Master's Program. Postgraduate Program. State University of Manado. Supervisor I: Prof. Dr. Shelty DM Sumual, M.Sc. Supervisor II: Prof. Dr. Henny Nikolin Tambingon, M.Pd. This study aims to analyze the influence of principal managerial competence and teacher work motivation on teacher performance at SMP Negeri 1 Airmadidi. The research problem is motivated by several indicators of low teacher performance, such as a lack of variety in teaching methods, low initiative in self-development, and delays in completing instructional administration. These conditions highlight the need for the principal's leadership role and an increase in teacher motivation to support performance improvement. This study employs a quantitative approach. The population in this study consists of all 40 Civil Servant (ASN) teachers at SMP Negeri 1 Airmadidi. Data collection was conducted through Likert-scale questionnaires and subsequently analyzed using multiple linear regression analysis. The results show that principal managerial competence has a positive and significant influence on teacher performance, with a t-count of 3.067 > t-table 2.051 and a significance level of 0.004 < 0.05. Teacher work motivation also has a positive and significant influence on teacher performance, with a t-count of 4.282 > t-table 2.051 and a significance level of 0.001 < 0.05. Furthermore, simultaneously, principal managerial competence and teacher work motivation have a significant effect on teacher performance with an F-count (9.97) > F-table (3.35) and a significant value of 0.001 < 0.05. Based on these results, it can be concluded that principal managerial competence and teacher work motivation play a crucial role in improving teacher performance. Therefore, principals are expected to continuously enhance their managerial skills in managing schools and provide support that can boost teacher motivation, thereby improving the quality of learning in schools. Keywords: Principal Managerial Competence, Teacher Work Motivation, Teacher Performance.